2018
DOI: 10.3389/fpsyt.2018.00067
|View full text |Cite
|
Sign up to set email alerts
|

Brain Structures Associated with Internet Addiction Tendency in Adolescent Online Game Players

Abstract: With the development of the Internet, an increasing number of adolescents play online game excessively, which leads to adverse effects on individuals and society. Previous studies have demonstrated altered gray-matter volume (GMV) in individuals with Internet gaming disorder (IGD), but the relationship between the tendency to IGD and the GMV across whole brain is still unclear in adolescents. In the present study, anatomical imaging with high resolution was performed on 67 male adolescents who played online ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 66 publications
1
32
0
2
Order By: Relevance
“…Through careful examination and scoring, the subjects with IGD were selected according to the following criteria: (1) the IAT score was 80 or above; (2) the IGAS score was 7 or above; (3) the type of Internet game played was mainly "Strike of Kings"; and (4) a clinical interview was administered by two psychiatrists to diagnose IGD in accordance with DSM-5. The subjects as control group were selected according to the following criteria: (1) the IAT score was 40 or below; (2) the IGAS score was 3 or below; (3) the type of Internet game played was mainly "Strike of Kings." A total of 15 male college students with "Strike of Kings" game addiction were recruited into the IGD group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through careful examination and scoring, the subjects with IGD were selected according to the following criteria: (1) the IAT score was 80 or above; (2) the IGAS score was 7 or above; (3) the type of Internet game played was mainly "Strike of Kings"; and (4) a clinical interview was administered by two psychiatrists to diagnose IGD in accordance with DSM-5. The subjects as control group were selected according to the following criteria: (1) the IAT score was 40 or below; (2) the IGAS score was 3 or below; (3) the type of Internet game played was mainly "Strike of Kings." A total of 15 male college students with "Strike of Kings" game addiction were recruited into the IGD group.…”
Section: Methodsmentioning
confidence: 99%
“…The experiment allowed us to comprehensively investigate the neurocognitive mechanisms in the unconscious and automatic condition. We hypothesized that (1) individuals with IGD exhibit a significantly larger P100 peak amplitude when elicited by cartoon faces than when elicited by realistic faces and a significantly larger P100 peak amplitude of cartoon faces than healthy individuals; (2) individuals with IGD exhibit a significantly larger N170 peak amplitude when elicited by cartoon faces than when elicited by realistic faces and a significantly larger N170 peak amplitude of cartoon faces than healthy individuals; (3) individuals with IGD exhibit a significantly larger P200 peak amplitude when elicited by cartoon faces than when elicited by realistic faces and a significantly larger P200 peak amplitude of cartoon faces than healthy individuals; (4) the MMN amplitudes of individuals with IGD elicited by cartoon faces are significantly larger than those elicited by realistic faces, and individuals with IGD show a significantly larger MMN amplitude of cartoon faces than healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In adolescents, IGD was associated with changes in gray-matter volumes in brain regions involved in sensory-motor processes and cognitive control 19 evaluating reward, error processing, and adjusting behavior, 20 impulse control, attention, emotional regulation, and motor function. 11 Reduced gray-matter volume was reported in the prefrontal cortex and the amygdala, and the volume of these regions was associated with measures on the Barratt Impulsiveness Scale.…”
Section: Imaging Studies On the Brain’s Gray-matter Volume And White-mentioning
confidence: 99%
“…There is increasing evidence that, in its extreme, excessive media usage can also lead to behavioral addiction, This seems to be particularly the case for internet gaming. Studies examining the neuronal consequences of internet gaming disorder reported numerous significant changes (99,100), including alterations in resting-state EEG coherence (101), significant alterations in cortical thickness (102,103), altered functional connectivity in the default mode network (104,105), and significant associations with ADHD and other psychiatric disorders (106,107). As they now stand, these findings are correlational and cannot establish causation.…”
Section: Studying the Effects Of Media Overusementioning
confidence: 99%